Partisipasi Stakeholders Islam dalam Upaya Mereformasi Peraturan Daerah tentangUsaha Tempat Hiburan di Kota Probolinggo - Imam Sucahyo (Publisia: Jurnal Ilmu Administrasi Publik, 2017)
The nightlife scene is inevitable. Through Perda Kota Probolinggo Number 9 of 2010 it is regulated. However, in its development, it has little impact on society; Covert prostitution, the circulation of liquor, disputes between visitors, and moral decadence, made the Islamic stakeholders critical of guarding the local regulation, until finally the new law was born. This paper seeks to see how the participation of stakeholders labeled Islam ultimately succeeded in reforming this policy. The method in this research is descriptive qualitative with focus on three Islamic stakeholders, which are in the policy arena, outside policy but formal and outside but informal. Data is taken through observation, interview and documentation. Methods of data analysis using interactive analysis model Miles and Huberman. The results concluded; 1) Partisiapasi of Islamic stakeholders in the policy area conducted by the PKB and PPP factions joined in Commission X. Through the legislative authority of this group proposed Raperda after previously hearing and cooperating with LPPMUB. Supervision authority is carried out by recommendation. 2) The participation of Islamic stakeholders outside the policies incorporated in the main formal organization comes from NU circles. The group is pro actively guarding every phenomenon as a result of the enactment of local regulations, starting letters of recommendation, joining in the hearing, giving moral support to the Police, and so on. 3) The participation of Islamic stakeholders outside the policy sphere and not directly incorporated in formal organizations is used as the last ammunition through demonstration media.DOI: https://doi.org/10.26905/pjiap.v2i2.1939